Pengaruh Perceived Risk, Trust, Dan Information Seeking Terhadap Perilaku Konsumen (Studi Pada Brand Erigo Di Shopee) - Agustina, Vita .; Bahri, Halida . (Jurnal Visioner & Strategis, 2024)
Online shopping is currently quite popular among Indonesian people, the presence of e-commerce makes it easier for consumers so that consumers prefer online shopping. One of the things that consumers are most interested in when shopping online is the fashion category, the fashion brand that consumers are interested in is Erigo. This is proven by Erigo sales on Shopee which continue to increase in the 2020-2022 period. Erigo is a local brand that attracts a lot of attention from consumers, as well as consumers in Lhokseumawe City. Consumer behavior in choosing Erigo is believed to be influenced by several factors. This research aims to determine the influence of perceived risk, trust, and information seeking on consumer behavior. The method used is a quantitative research method. The population in this research is the people of Lhokseumawe City who buy the Erigo brand on Shopee. The sample consisted of 100 respondents. The research results show that perceived risk, trust, and information seeking have a significant effect on consumer behavior in purchasing the Erigo brand on Shopee. Based on the results of the F test, it was found that the significance value was 0.003 < 0.05 and the F value was 3.239 > F table 2.699 so that simultaneously there was an influence between perceived risk, trust and information seeking on consumer behavior in buying the Erigo brand at Shopee. The relationship between these variables is amounting to 80.7% while the remaining 19.3% was influenced by other variables not examined in this research. Keywords: Perceived Risk, Trust, Information Seeking, Consumer Behavior